Towards functional antibody-based vaccines to prevent pre-erythrocytic malaria infection - Brandon Sack; Stefan H.I. Kappe; D. Noah Sather (Taylor & Francis Group, 2017)
Introduction: An effective malaria vaccine would be considered a milestone of modern medicine, yet has so far eluded research and development efforts. This can be attributed to the extreme complexity of the malaria parasites, presenting with a multi-stage life cycle, high genome complexity and the parasite's sophisticated immune evasion measures, particularly antigenic variation during pathogenic blood stage infection. However, the pre-erythrocytic (PE) early infection forms of the parasite exhibit relatively invariant proteomes, and are attractive vaccine targets as they offer multiple points of immune system attack. Areas covered: We cover the current state of and roadblocks to the development of an effective, antibody-based PE vaccine, including current vaccine candidates, limited biological knowledge, genetic heterogeneity, parasite complexity, and suboptimal preclinical models as well as the power of early stage clinical models. Expert commentary: PE vaccines will need to elicit broad and durable immunity to prevent infection. This could be achievable if recent innovations in studying the parasites' infection biology, rational vaccine selection and design as well as adjuvant formulation are combined in a synergistic and multipronged approach. Improved preclinical assays as well as the iterative testing of vaccine candidates in controlled human malaria infection trials will further accelerate this effort.